TYPOLOGICAL STUDY OF COMPOUND SENTENCES IN WORLD LINGUISTICS (International journal of artificial intelligence, 2026)
This article provides a scientific analysis of the typological study of compound sentences in world linguistics based on Arabic language materials. The research examines the structural, semantic, and functional features of compound sentences in Arabic from a comparative-typological perspective. The syntactic structure, grammatical markers, and communicative-pragmatic functions of coordinated, subordinate, and mixed compound sentences are explored in detail. Models of compound sentences in Arabic are compared with syntactic units in other languages to identify their universal and language-specific characteristics. The article also analyzes the role of compound sentences in text formation, their functional significance in discourse, and theoretical approaches within syntactic typology.